The Forms of Implantation of Foreign Banks in Algeria: Evolutions of Practices and Effects on External Financial Risks - Gamache , Nadjib (Finance and Business Economies Review, 2023)
Algeria has experienced deep mutation of its relations with foreign banks. The forms of establishment of those banks in the country have adjusted to economic and political changes, moving from cross border claims to local claims through branches and subsidiaries. This change went with a mitigation of direct financial risks associated to external financing of the economy. First, less indebted since the mid 1990s ,Algeria is more independent financially. Second, the external financing through foreign bank’s local affiliates, in local currency is more stable because locally funded.